The within-participant correlation between perception of effort and heart rate-based estimations of training load in elite soccer players - Kelly, D. M.; Strudwick, A. J.; Atkinson, G.; Drust, B.; Gregson, W. (Journal of Sports Sciences, 2016)
The measurement of relative physiological stress during training is important because this is the stimulus for the long-term adaptive response. Measurements of perceived exertion (RPE) have been reported to correlate with the heart rate during field-based training sessions. Nevertheless, there are few studies on how well RPE tracks with the heart rate over repeated training sessions in elite soccer players. Therefore, we aimed to quantify the within-participant correlations between variability in session-RPE (sRPE) and the heart rate in elite male soccer players, and to determine whether the playing position moderated these correlations. The field-based training of four central defenders, four wide defenders, six central midfielders, two wide midfielders and three attackers from an elite English Premier League squad were monitored over an entire in-season competitive period, giving a total of 1010 individual training sessions for study. Correlations between session-RPE and heart rates were quantified using a within-participant model. The correlation between changes in sRPE and heart rates was r = 0.75 (95% CI: 0.71-0.78). This correlation remained high across the various player positions (wide-defender, r = 0.81; central-defender, r = 0.74; wide midfielder, r = 0.70; central midfielder, r = 0.70; attacker, r = 0.84; P < 0.001). The correlation between changes in RPE and heart rates, measured during a season-long period of field-based training, is high in a sample of elite soccer players.